A phenomenological study of consumer perceptions and industry challenges in the transition to sustainable packaging - Melvin N. Espineda; Angelo H. Banocnoc; Ian Boots B. Bautista (Discover Sustainability)
Abstract Packaging shapes consumer behavior functionally as much as aesthetically. Initially, it was just a protective measure, but it has now become a primary marketing tool. Many consumers prioritize price, convenience, and design over sustainability, despite an increasing environmental consciousness. Due to durability and usage issues, environmentally friendly choices such as reusable bags and biodegradable plastics face difficulty in gaining acceptance. Environmentally friendly alternatives, such as biodegradable plastics and reusable bags, are hindered in adoption due to durability issues. This study employs a phenomenological research approach and the modified Stevick-Colaizzi-Keen Method to investigate the lived experiences of eco-bag users, graphic designers, and sustainability advocates in Metro Manila. It identified four key themes affecting sustainable packaging adoption: (1) Enhancing Durability for Sustainability, Safety, and Efficiency; (2) Using Minimalist Design in Eco Bags to Enhance Appeal and Sustainability.; (3) Implementing Widespread Adoption of Eco-Bags through Clear Policies and Guidelines; and (4) Using and Promoting Recyclable and Natural Raw Materials in Eco-friendly Bag Packaging. The results underscore the need for collaboration among businesses, legislators, and designers to eliminate barriers to sustainable packaging. A comprehensive approach that emphasizes durability, simplicity, control, and environmentally friendly materials can increase customer involvement and foster broader acceptance.